An ethical advantage of autistic employees in the workplace - Hartman, Lorne; Hartman, Braxton (Frontiers in Psychology, 2024)
Differences between autistic and nonautistic people are often framed as deficits. This research considers whether some of these differences might actually be strengths. In particular, autistic people tend to be less sensitive to their social environment than nonautistic people who are easily influenced by the judgments, opinions, beliefs and actions of others. Because autistic people are less susceptible to social influence, as employees they are more likely to take action when they witness an operational inefficiency or an ethical problem in the organization. By reporting problems, autistic employees may contribute to the introduction of innovations and improvements in organizational processes and effectiveness that result in superior performance. This paper considers whether and the extent to which these differences between autistic and nonautistic employees are moderated by “moral disengagement,” a set of interrelated cognitive mechanisms that allow people to make unethical decisions by deactivating moral self-regulatory processes. While previous research has shown that moral disengagement is related to unethical decisions, there is no research on whether and the extent to which autistic people are vulnerable to moral disengagement. Thirty-three autistic employees and 34 nonautistic employees completed an on-line survey to determine whether differences between autistic and nonautistic employees with regards to (1) likelihood they would voice concerns about organizational dysfunctions, and (2) degree to which they were influenced by the presence of others when deciding to intervene, are moderated by individual differences in moral disengagement. As predicted, autistic participants scored lower on moral disengagement than nonautistic participants. In terms of the moderating effects of moral disengagement, the results are mixed. Although moral disengagement reduced intervention likelihood, there was not a difference between autistic and nonautistic employees in the degree to which intervention likelihood was changed by an individual’s level of moral disengagement. However, there was a difference between autistic and nonautistic employees in the extent to which acknowledging the influence of others was affected by moral disengagement. These findings suggest that autistic adults are not just more likely to intervene when they witness dysfunction or misconduct in an organizational context; they are also less likely to engage in unethical behavior in general due to lower levels of moral disengagement. The reduced susceptibility to the bystander effect evidenced by autistic adults in the workplace may be accounted for, in part, by their lower levels of moral disengagement compared with nonautistic adults.